Cooperative learning for the implementation of deep learning to enhance students’ reading skills - Luthfiansyah, Ananda Poetri; Astuti, Puji (ELT Forum: Journal of English Language Teaching, 2025)
Reading is one of the important skills in learning English because it is a window to knowledge and a foundation for developing other language skills. However, students' reading skills in Indonesia remain low due to various factors, coupled with reading learning that still tends to be shallow and focused on memorization. Therefore, a learning strategy is needed that focuses not only on the final result but also on the thinking process and deep understanding. Although both Deep Learning and Cooperative Learning have proven effective in enhancing reading skills, there has been no research examining how Cooperative Learning can be used as a method for implementing the Deep Learning approach. Therefore, this article aims to explore how Cooperative Learning can be used as a method for implementing the Deep Learning approach to enhance reading skills. This article uses a library research method with a focus on the Jigsaw type as a representation of Cooperative Learning that implements Deep Learning. Jigsaw implements the principles of mindful learning through conscious and attentive student involvement, meaningful learning through linking information from the text to personal experiences, and joyful learning through a collaborative and enjoyable learning atmosphere. In conclusion, Cooperative Learning can serve as a method for implementing Deep Learning to enhance students' reading skills. The implications of this article can serve as a reference for teachers in optimizing teaching reading and can also be the basis for empirical research in the future.